CRITICAL DISCOURSE ANALYSIS ON PRINTED CIGARRETTE ADVERTISEMENT - Ariani, Sri (Menara Ilmu, 2019)
This paper tries to analysethe linguistic features used in cigarette advertisementsand their relations with social and cultural development as well as the power showed bythe discourse used in cigarette advertisements. The research uses descriptive qualitativemethod by using content or document analysis. The analysis adopts Fairclough’s CriticalDiscourse Analysis (CDA) framework. The result shows that many printed cigarette adscan often be interpreted negatively because their ideas are often related to capitalism andnot reflect the eastern culture. The company in fact should build positive image in theminds of public. They should not only make the advertisements as catchy as possible butalso consider about the effect of the language in the public interpretation. The ads vieweras consumers should aware of the manipulating language of advertisement that can affectthe social and cultural aspects.Keywords:Fairclough’s Critical Discourse Analysis, Cigarette Advertisement